Investigating the social configuration of a community to understand how networked learning activities take place: The OERu case study - Schreurs, Bieke; Van den Beemt, Antoine; Prinsen, Fleur; De Laat, Maarten; Witthaus, Gabi; Conole, Gráinne (Proceedings of the International Conference on Networked Learning, 2014)
Examining how OER (Open Educational Resources) communities come to live, function or learn can support in empowering educators in the use of open educational resources. In this paper we investigate how an OER community functions through its networked learning activities. Networked learning activities enable the development of a space (a social configuration) for shared activity, in which learning by participants is situated. Following existing research on the social configuration of learning communities, we operationalize this space into four superordinate dimensions: (1) domain and value creation, (2) practice (3) collective identity and (4) organisation. We argue that these dimensions add to an understanding of the functionality of learning communities, in this case OER communities. An in-depth case study was conducted of the OER university (OERu) (www.wikieducator.org/oeru). The OERu is a virtual collaboration of institutions committed to creating flexible pathways for OER learners to gain formal academic credit (WikiEducator, 2013). A mixed-methods approach was used combining data from social network analysis, content analysis, and contextual analysis. Both volunteers and academic contributors from the 26 partner institutions were involved in the study. The results show how networked learning activities are associated with the social configuration (domain - identity - practice - organisation) of the community and that, through the investigation of this configuration, valuable insights can be gained into why networked learning activities are occurring. We see for example that shared domain could provide a solid ground for networked learning activities within a community and that different identities within the community can result in different networked learning activities. By analysing the organisation of the community, different social configurations were unravelled with different roles, goals and learning platforms. These insights may support the OERu community and other OER communities to develop their networked learning activities further in a sustainable way.